2017
DOI: 10.1097/bot.0000000000000763
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Computed Tomography in Surgical Planning for Trimalleolar Fracture. A Survey of OTA Members

Abstract: Diagnostic Level V. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 25 publications
0
9
0
3
Order By: Relevance
“…Therefore, CT imaging is recommended to evaluate fractures, their anatomical relationships, extent of comminution and intra-articular bodies in ankle injuries (4). Moreover, CT imaging has been shown to be useful in cases of dislocated fractures, fractures that may be obscure on XR due to cast, trimalleolar fractures and suprasyndesmotic fractures (6).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, CT imaging is recommended to evaluate fractures, their anatomical relationships, extent of comminution and intra-articular bodies in ankle injuries (4). Moreover, CT imaging has been shown to be useful in cases of dislocated fractures, fractures that may be obscure on XR due to cast, trimalleolar fractures and suprasyndesmotic fractures (6).…”
Section: Discussionmentioning
confidence: 99%
“…In a study, preoperative CT was shown to significantly alter the surgical strategy in 24% of malleolus ankle fracture cases (6). In a study comparing the treatment of trimalleolar ankle fracture before and after CT, it was shown that the surgical planning, technique and approach of a surgeon frequently changed with additional information provided by CT, and that radiographs alone were insufficient to determine the characteristics of a fracture (5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…En cuanto a las pruebas complementarias preoperatorias, recientemente Gibson ha observado que más de un 25% de los cirujanos cambia su estrategia terapéutica después de analizar las imágenes de TC, por lo que recomienda su utilización en la planificación de todas las fracturas trimaleolares 12 . Esto iría en concordancia con el hecho de que casi la mitad de los cirujanos de pie y tobillo en el presente estudio solicitarían TC en dicho tipo de lesiones.…”
Section: Discussionunclassified
“…Otro inconveniente, por tanto, de la estrategia anatómica es que se hace necesaria una planificación preoperatoria más exquisita que en el enfoque clásico, donde las decisiones se toman intraoperatoriamente y no se tratan de forma directa algunos componentes de la lesión, por lo que sería preceptiva la indicación de TC para la correcta observación y clasificación de todas las estructuras lesionadas que necesitamos reparar (29) , algo que no se admite en todos los centros de nuestro medio.…”
Section: Enfoque Actual De Reparación Anatómica Directaunclassified